Technical and economic assesment of radier foundation for a unifamiliary habitation (Research, Society and Development, 2021)
Foundation is one of the most important structural elements of a building and it is responsible to transfer the building loads to a hard layer of soil. Foundations can be divided in superficial and deep foundations. The radier is a type of surface foundation, which consists of a concrete slab that evenly distributes the loads of the building to the ground. The objective of this article comprises the comparation of constructive techniques of the radier-type foundation, in relation to the isolated footing foundation, by means of an economic technical analysis between the two types of surface foundations, in order to define the one with the best constructive viability. A case study of a single-family residential building was used in this research. A previously dimensioned design in isolated footing foundation was used and a structural design of the radier foundation was carried out in the same building, using Eberick software. Based on the results, budget spreadsheets were prepared with reference values ​​based on the SINAPI Regional Table and Physical Schedules. The same team of masons and working hours were considered for both methods. According to the results obtained, in relation to cost and time, the isolated footing is more expensive and time consuming than the radier. Thus, it is possible to conclude that the radier type foundation has an excellent performance in relation to the isolated footing, because when it is well dimensioned, it can provide better technical and economic viability for the foundation, which is one of the most important structural elements of the building. It should be noted that this analysis is restricted to this case study, however, the results obtained are supported by the literature.